PENDIDIKAN ISLAM TERPADU, MENCARI MODEL PEMBELAJARAN KOMPREHENSIF - Khoiruddin Bashori (Islamic University of Indonesia, 2002)
The industrialization implies the changing of many aspects of human life. One of them tends to emerge the orientation of materialism and its consumerism. If this phenomena cannot overcome, can threaten the balancing between inner worldly and otherworldly. The phenomena, particularly the social facts that happen recently, cause rising of parents' afraid of their children's future. In this sense, the emergence of Sekolah Islam Terpadu - The integrated Islamic School becomes an alternative to overcome the problems aforementioned, because it integrates the concept of Islamic education and the method of modern education. We expect that the Integrated Islamic School can become an alternative solution effectively, it is needed to change the approaches of education- from traditional approach to accelerated learning. In this context, there are four important components in accelerated learning. The combination of four components that often called SAVI, namely Somatic (learning by moving and doing), Auditory (learning by talking and hearing), Visual (learning by observing and picturing), and Intellectual (learning by problem and reflecting). But the problem that faced by the Integrated Islamic School is how to pay more attention to affective education.